2020
DOI: 10.1111/nmo.13869
|View full text |Cite
|
Sign up to set email alerts
|

Diet differentially regulates enterochromaffin cell serotonin content, density and nutrient sensitivity in the mouse small and large intestine

Abstract: Background Enterochromaffin (EC) cells are specialized enteroendocrine cells lining the gastrointestinal (GI) tract and the source of almost all serotonin (5‐hydroxytryptamine; 5‐HT) in the body. Gut‐derived 5‐HT has a plethora of physiological roles, including regulation of gastrointestinal motility, and has been implicated as a driver of obesity and metabolic disease. This is due to 5‐HT influencing key metabolic processes, such as hepatic gluconeogenesis, adipose tissue lipolysis and hindering thermogenic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The finding is also in line with a part of clinical studies showing an association of long-term SSRI use with an increased risk of developing obesity [30,31]. However, there is no consensus in the literature regarding circulating serotonin levels in obesity, with studies reporting both positive [41][42][43][44] and negative [45][46][47][48] or no [48,49] associations between blood 5HT parameters and body mass index/body fat. The relationship between circulating 5HT levels and obesity is mostly studied by measuring the platelet 5HT pool, while data on biologically active 5HT in blood plasma and activity of platelet 5HT transporter are scarce.…”
Section: Discussionsupporting
confidence: 81%
“…The finding is also in line with a part of clinical studies showing an association of long-term SSRI use with an increased risk of developing obesity [30,31]. However, there is no consensus in the literature regarding circulating serotonin levels in obesity, with studies reporting both positive [41][42][43][44] and negative [45][46][47][48] or no [48,49] associations between blood 5HT parameters and body mass index/body fat. The relationship between circulating 5HT levels and obesity is mostly studied by measuring the platelet 5HT pool, while data on biologically active 5HT in blood plasma and activity of platelet 5HT transporter are scarce.…”
Section: Discussionsupporting
confidence: 81%
“…Serotonin is also known to have numerous functions, such as smooth muscle contraction of blood vessels and bronchi, acceleration of peristaltic movement (Berger et al, 2009), respiratory rhythm (Cinelli et al, 2020), regulation of β cells in the pancreas (Berger et al, 2009;Li et al, 2000), liver regeneration (Inoue et al, 2018;Kamimura et al, 2018), liver fibrosis (Kyritsi et al, 2020), protection against intestinal ischemia (Tackett et al, 2019) and food-seeking behavior (He et al, 2020), and its reuptake inhibitors are used as an antidepressant in relation to gastrointestinal symptoms (Salisbury et al, 2020). In addition, serotonin is reportedly involved in the fibrosis of NAFLD (Atallah et al, 2018), the modification of lipid metabolisms (Namkung et al, 2018), the activation of signal from serotonin receptor on the hepatocytes (Choi et al, 2018), and the modulation of autophagy and Notch signal (Martin et al, 2020). Interestingly, Haub et al (2011) reported that the blockade of the serotonin receptor HTR3, which is the receptor expressed in the intestine, modified the strength of the tight junction and improved the obesity-associated fatty liver in mice.…”
Section: Discussionmentioning
confidence: 99%
“…ECs act as important luminal sensors within gastrointestinal tract and can sense several nutrient stimuli and secrete 5-HT in response to luminal sugars [ 62 , 112 ]. In humans, the sensing of glucose is altered with obesity and the researchers assessed that the mice feed with high fat (HFD) diet began obese [ 112 , 113 , 114 ]. Martin et al (2020) showed that HFD-feeding alters the sensing of ECs in a region-dependent manner involving duodenum but not colon.…”
Section: Enterochromaffin Cells and Diet In Pathologymentioning
confidence: 99%